The Role of Psychotherapeutic Intervention in the Disorganised Family - Moisa, Valentina-Beatrice (New Trends in Psychology, 2023)
The role of psychotherapeutic intervention of the family in impasse at a given moment, leads to a new understanding of the impediments encountered by its members, also, on the meaning of suffering during the family life story, accessing personal history.